Dari Tobat Privat ke Akuntablitas Publik: Konstruksi Tobat dalam Tafsir Syu'bah Asa - Al Vinatul Kharimah; Ghina Ariqah (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2025)
This article examines the construction of repentance in Syu’bah Asa’s socio-political Qur’anic interpretation, focusing on his discussion of repentance in Dalam Cahaya Al-Qur’an: Tafsir Ayat-Ayat Sosial Politik. The study departs from the observation that repentance is often framed as a private spiritual experience, whereas Syu’bah Asa articulates it as a public ethic that binds both political leaders and citizens. Employing a qualitative library-based approach, the paper conducts an interpretive reading of the text by identifying key themes and tracing argumentative patterns. The findings indicate that Syu’bah Asa defines repentance through socially verifiable actions, particularly the restoration of public rights, accountability for unjust gains, and a concrete commitment to rectify abusive practices and public policies. He develops the notion of structural repentance, namely a form of repentance directed at systemic wrongdoing such as corruption, the suppression of civil liberties, and the abuse of power, thereby rejecting purely symbolic religiosity or verbal remorse as sufficient. These results position Syu’bah Asa’s tafsir as a transformational mode of interpretation that links Qur’anic spirituality to public accountability and socio-political reform.